Neuropathic foot ulcer: microbiological assessment in chronic osteomyelitis - Lima, Ana; Rosemberg, Dov; Oliveira, Priscila; Saito, Guilherme; Macedo, Rodrigo; Sposeto, Rafael; Godoy-Santos, Alexandre; Fernandes, Tulio (Journal of the Foot & Ankle, 2021)
Objective: To determine the microbiological profile and antimicrobial susceptibility patterns of organisms isolated from chronic osteomyelitis secondary to neuropathic foot ulcers; secondarily, to describe the clinical outcomes of 52 patients admitted to a neuropathic foot referral center. Methods: Retrospectively chart review of 52 patients with clinically infected neuropathic foot ulcers admitted to our service for treatment between 2005 and 2013. Tissue samples were collected for culture at the operating room after extensive debridement in order to determine the infectious agents and their resistance profile using the disk-diffusion technique, following CLSI criteria. Results: A total of 52 patients were analyzed (40 males and 12 females). The mean age was 58 (37-72) years. Each patient presented with an average of 2.13 microorganisms, distributed as follows: 51% Gram-positive cocci, 43% Gram-negative bacilli. Among Staphylococcus aureus isolates, the prevalence of methicillin resistance was almost 50%, and the prevalence of coagulase-negative staphylococci (CoNS) was more than 75%. Conclusion: S. aureus, E. faecalis, and CoNS were the most frequently isolated pathogens. Methicillin resistance was highly prevalent. A combination of extensive surgical debridement and prolonged antimicrobial therapy led to remission of infection in 77% of patients. Level of Evidence IV; Therapeutic Studies; Case Series.